Integrating Picture Sequence and Question-Answer Relationship (QAR) Enhances EFL Students’ Narrative Reading Comprehension - Ismi Farida (Universitas Negeri Surabaya, 2026)
Comprehending English texts remains challenging for EFL learners, as they often struggle to grasp the overall idea, particularly when dealing with lengthy texts and unfamiliar vocabulary. To address this issue, the present study combines Picture Sequence with the Question–Answer Relationship (QAR) strategy to support students’ reading comprehension. This integrated approach helps students visualize story events while guiding them to answer comprehension questions more purposefully. Using a quasi-experimental design involving 72 tenth-grade students, learners taught through the integrated strategy showed greater improvement in narrative reading comprehension (mean = 67.08–80.14) than those receiving conventional instruction (mean = 70.00–75.14). Although the improvement was moderate (Cohen’s d = 0.50), it reflected a meaningful enhancement in students’ ability to understand narrative content and respond accurately to comprehension questions. Based on the findings, the combined strategy can be considered a practical and effective approach for improving narrative reading comprehension in EFL classroom settings.